Penerapan Activity Based Costing Dalam Penentuan Harga Kamar Rawat Inap (Studi Empiris Di RSUD Sumedang) - Evan Firdaus; Dady Nurpadi (Jurnal Co Management, 2020)
Activity Based Costing is an appropriate method in calculating basic costs. The benefits of Activity Based Costing are as a method or cost control system that tracks various activities that occur. Activity Based Costing is a system of cost calculation approaches based on activities in the company. Cost drivers used in this study as a cost grouping are the number of inpatient days, the number of inpatients, and the floor area of ​​the room. This study uses a comparative approach between conventional methods and Activity Based Costing methods. This research instrument uses observation, interview and documentation techniques. The results of inpatient service tariff calculations that have been set by Sumedang District Hospital for VIP class are Rp.821,100, for Class III Rp. 234,750, for class II Rp. 263,200, and for class I Rp. 319,000. While using the Activity Based Costing method gives different results, namely Rp. 336,365,085 for the VIP class, Rp.172,196.4 for the third class, Rp. 190,072,304 for class II, and Rp. 200,837,52 for class I. Using the Activity Based Costing method at Sumedang District Hospital gives smaller results (undercosting) for each class (VIP class, class III, class II, and class I) of hospital rates by having a difference of Rp. 484,734,085 for VIP class, for class III amounting to Rp. 62,553.6, Rp. 73,127,696 for class II, and Rp. 118,162.48 for class I.